Health professional perspectives on an antenatal mental health screening program in a private hospital. (13th June 2021) - Kohlhoff, Jane; Cibralic, Sara; Tooke, Sarah; Hickinbotham, Rachael; Knox, Catherine; Roach, Vijay; Barnett, Bryanne
Abstract : Background: Perinatal mental ill‐health is a global health priority. Mental health screening during pregnancy is a routine part of clinical practice in many public hospital obstetric services across Australia, but implementation in the private hospital system has lagged. Aims: This study explored health professionals' perspectives on the Pre‐admission Midwife Appointment Program (PMAP), an antenatal mental health screening program at the Mater Hospital, Sydney. Materials and Methods: Nine midwives and three medical specialists participated in focus groups or individual interviews; key themes were determined using thematic qualitative analysis. Results: Five major themes and three sub‐themes were identified: immediate benefits to women (identifying women at risk; referrals to support services; supporting and educating women); enhanced overall quality of care at the hospital; the dilemma of partners attending; factors that make the program successful; and recommendations for improvement. Conclusions: Results will inform the implementation of antenatal mental health screening programs at other private hospitals across Australia.